Mainstream versus special needs educators: comparisons of knowledge levels towards their roles and responsibilities in supporting inclusive education - Mah, Joanna Tjun Lyn; Loh, Sau Cheong; Noor Aishah Rosli (Penerbit Universiti Kebangsaan Malaysia, 2020)
With inclusive systems requiring major transformation and metamorphosis to educators’ traditional responsibilities, extensive shifts to these “inclusive roles” are becoming a problem for both mainstream and special needs educators who find themselves in dexterous, multifaceted, overlapping and clashing responsibilities. This study examined and compared the knowledge levels of 608 mainstream and special needs educators across Malaysia towards their roles and responsibilities in supporting inclusive education in Malaysian primary schools in three stages, namely the pre-transition during transition, and post-transition stage. Questionnaire was constructed to collect data, and the data obtained was analysed descriptively. Findings indicated a general lack of knowledge among mainstream educators and special needs educators in all stages of the transition process, which is symptomatic that both groups of educators are beyond their capabilities, competencies and incontrovertibly their skills and knowledge in inclusive education. Furthermore, findings revealed that the special needs educators are marginally more knowledgeable in supporting inclusion as compared to the mainstream educators at all stages of inclusive transitions. The findings implicate that the transformation from traditional roles to modern inclusive job roles interfere with the comparison in knowledge levels between both mainstream and special needs educators and the lack of role clarity may be related to self-depreciating feelings and self-reports of lower confidence in their knowledge ability.